ESQ DAN KEBUTUHAN SPIRITUALITAS CIVITAS AKADEMIK - Hamid, Ilham (Jurnal Berita Sosial, 2018)
Essentially human beings are religious beings (homoreligius) and fithrahnya humans are spiritual beings who always strive to always exist in a healthy mental condition, in order to live happy, born and inner. It has the perfect spiritual intelligence potential to achieve ’spiritual wellness’, that is, the happiness of true life as a form of divine grace. That is why Guidance and Counseling services as a form of interpersonal relationships should adhere to religious values when helping, directing, and guiding individuals to develop spiritual intelligence to achieve meaningful life and complete and integrated happiness. Because religious values are fundamental, absolute, and universal. Keywords: ESQ, Spiritual Intelligence